Engineering a spatiotemporal macrophage circuit via STING phase separation to override immune suppression in pancreatic cancer - Xue Yang; Yinlu Wang; Jiaxin Zhou; Siyu Li; Jin Ye; Yu Sun; Mengning He; Kai Fan; Zixin Chen; Fangzheng Tian; Ben Zhao; Jianqiong Zhang; et al. (Proceedings of the National Academy of Sciences, 2025)
Pancreatic ductal adenocarcinoma (PDAC) remains one of the most lethal malignancies, largely due to its highly immunosuppressive tumor microenvironment (TME), which fuels metastasis and resistance to immunotherapy. Through comprehensive analysis of single-cell RNA sequencing datasets, we identified multiple heterogeneous tumor-associated macrophage (TAMs) subpopulations as key regulators of PDAC progression, which coexpress MRC1 and exert their effects by actively suppressing antitumor immune responses. To overcome this barrier, we developed a spatiotemporal macrophage reprogramming platform that leverages STING phase separation to reprogram TAM plasticity and reshape the immune landscape. This system, MRC1-targeting peptide–M@BLZ945 (PMMB), integrates a colony-stimulating factor 1 receptor (CSF-1R) inhibitor and a STING agonist within a macrophage-mimetic nanostructure, enabling sequential, controlled reprogramming of TAMs. By leveraging STING phase separation, PMMB stabilizes TAMs in an antitumor CD80 + phenotype while preventing excessive inflammation, achieving durable immune activation. In preclinical models, PMMB not only suppresses both primary and metastatic PDAC but also enhances CD8 + T cell infiltration, reinvigorates anti-PD-1 therapy responses, and mitigates immune exhaustion. These findings establish spatiotemporal macrophage circuit engineering via STING phase separation as a cross-scale strategy to override PDAC’s immune barriers and drive next-generation macrophage-targeted immunotherapy. This study paves the way for rationally designed, precision macrophage modulation strategies in solid tumors.